(untitled) (SCIENCE TIME JOURNAL, 2026)
The article examines the role and significance of terminology and terminography within the system of the modern Uzbek literary language, as well as their formation and development as independent fields of linguistic study. It highlights the emergence of terminological research in Uzbek linguistics since the early twentieth century, focusing on the issues of term standardization and the compilation of terminological dictionaries. The historical foundations of grammatical terminology are analyzed through the works of Mahmud al-Kashgari, Alisher Navoi, and Abdurauf Fitrat. Particular attention is paid to the structural characteristics of terms, the problem of multi-component terms, oppositional relations, and the systemic nature of grammatical terminology. The study emphasizes the importance of systematizing Uzbek grammatical terms and developing electronic terminological dictionaries in accordance with contemporary linguistic requirements.